Hormone–receptor expression status of epithelial ovarian cancer in Ibadan, South-western Nigeria (2017)
Introduction: epidemiological evidence strongly suggests that steroid hormones are implicated in the pathogenesis of ovarian cancer. Estrogen receptor (ER) and Progesterone receptor (PR) are prognostic indicators for a number of epithelial tumors and may play the same role in ovarian cancers. This study aims to evaluate the expression of ER and PR in epithelial ovarian cancer (EOC) in an African population and compare it with other prognostic factors such as age, International Federation of Gynaecology and Obstetrics (FIGO) stage, grade and histological subtype. Methods: ninety cases of histologically confirmed EOC were reviewed. Immunohistochemistry was used to assess their ER and PR expression status and was then compared with other demographic variables using statistical methods, with level of significance set at p < 0.05. Results: 30.2% and 8.3% of serous and mucinous carcinomas respectively were ER positive while 41.2% and 22.5% of both tumour types were PR positive. One of the two endometrioid carcinomas showed PR expression but neither were positive for ER. The only case of Brenner tumour in the series was ER positive but negative for PR. There was a significant association between ER and the histological subtypes (p=0.042) while no significant association was found between PR expression and histological subtypes (p =0.650). No significant association was found between hormone receptor status, age and stage of the EOC. Conclusion: the study showed a lower ER expression in serous carcinoma compared to large cohorts from developed countries. Future translational studies could be used to determine response of EOC to endocrine therapy